2016
DOI: 10.1111/acel.12498
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal insulin alleviates cognitive deficits and amyloid pathology in young adult APP swe/ PS 1dE9 mice

Abstract: SummaryBrain insulin signaling deficits contribute to multiple pathological features of Alzheimer's disease (AD). Although intranasal insulin has shown efficacy in patients with AD, the underlying mechanisms remain largely unillustrated. Here, we demonstrate that intranasal insulin improves cognitive deficits, ameliorates defective brain insulin signaling, and strongly reduces β‐amyloid (Aβ) production and plaque formation after 6 weeks of treatment in 4.5‐month‐old APPswe/PS1dE9 (APP/PS1) mice. Furthermore, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 44 publications
4
50
0
Order By: Relevance
“…APP/PS1 mice also showed reduced attention to themselves and the environment after evaluation via the open-field test in our study, in agreement with previous studies 27 , and these phenomena were alleviated by Akk treatment. The results of the Y-maze test showed that a high-fat diet further aggravated the impairment of learning and spatial memory ability in APP/PS1 mice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…APP/PS1 mice also showed reduced attention to themselves and the environment after evaluation via the open-field test in our study, in agreement with previous studies 27 , and these phenomena were alleviated by Akk treatment. The results of the Y-maze test showed that a high-fat diet further aggravated the impairment of learning and spatial memory ability in APP/PS1 mice.…”
Section: Discussionsupporting
confidence: 93%
“…APPswe/PS1dE9 (APP/PS1) double-transgenic mice and the parasite-free wild-type mice were purchased from the Model Animal Research Center of Nanjing University 27 . In order to clarify whether Akk works only under the conditions of high-fat diet, 3-month-old male APP/PS1 mice were fed ad libitum either a normal chow diet or a high-fat diet (Catalog no.…”
Section: Animal Modelmentioning
confidence: 99%
“…We found that intranasal insulin elevated the level of DCX in the brain of ICV-STZ rats compared to control rats, which suggested an increase in hippocampal neurogenesis. These results are consistent with our previous reports showing that intranasal insulin can enhance neurogenesis in the hippocampus of APP/PS1 mice50. Synapse loss is an early and invariant feature of AD and correlates well with cognitive decline4551.…”
Section: Discussionsupporting
confidence: 93%
“…4E). On the other hand, recent studies showed that intranasal insulin reduces cognitive decline and pathology in AD model animals [76,77]. These data suggest controversial effect of insulin on brain functions.…”
Section: Discussionmentioning
confidence: 98%